Artificial Intelligence Based Educational Game Design for Literacy and Numeracy Skills in Elementary School Mathematics Learning - Fitria Nur Hasanah; Fitria Eka Wulandari; Mahardika Darmawan Kusuma Wardana; Clarisa Seliya Tamara (Edu Komputika Journal, 2026)
Low literacy and numeracy achievement among elementary school students, particularly in mathematics learning, indicates the need for innovative learning media capable of providing adaptive and engaging learning experiences. Therefore, this study aims to design and evaluate an Artificial Intelligence (AI) based educational game for plane geometry learning to improve elementary school students' literacy and numeracy skills. The study employed the Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation. The developed product is an AI based Monopoly educational game that integrates adaptive question generation, automatic feedback, and learning analytics to adjust the difficulty level according to students' performance. The game was validated by two media experts and two mathematics education experts before being implemented in learning. The trial involved 25 fifth-grade students at Muhammadiyah 1 Labschool Umsida Elementary School. Data were collected through expert validation, classroom observation, and literacy and numeracy pretests and posttests. The validation results indicated that the developed game was highly feasible for classroom use. During implementation, students demonstrated high enthusiasm and active engagement in learning activities. The average pretest score increased from 65.64 to 80.16 in the posttest. The data met the normality assumption (pretest = 0.253; posttest = 0.567; p > 0.05). Furthermore, the Paired Sample t-test revealed a significant improvement in students' literacy and numeracy skills (p = 0.000), while the average N-Gain score of 40.07% indicated a moderate level of effectiveness. These findings demonstrate that the proposed AI based educational game is a feasible and effective learning medium for enhancing elementary students' literacy and numeracy skills while supporting Sustainable Development Goal 4 on Quality Education.